Analisis Implementasi Kebijakan Kurikulum Merdeka Belajar pada Jenjang Sekolah Menengah Pertama - Ragil Sri Wahyuningsih; Fatimatus Zahro; Nada Vanca Anggrestia; Mulia Putri Khasanah; Asih Andriyati Mardliyah (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study aims to find out how the Merdeka Learning curriculum is implemented and the challenges that must be faced in the implementation process. This type of research is a type of qualitative research by applying the literature study method by reviewing 5 national journals and 1 international journal that are relevant to the topics discussed. The stages carried out by the author in collecting data or information are by (1) finding and collecting reading material that is relevant to the main topics discussed, and (2) analyzing the reading material then drawing conclusions based on the main topic. The results of the study show that the process of implementing the curriculum at the junior high school level will run optimally if the teacher and the school understand in depth the concept of the Freedom to Learn curriculum and the presence of various supporting parties such as the community to student guardians. The challenges that become obstacles in the implementation of this curriculum are teachers who do not understand the concept of the Free Learning curriculum, limited facilities and infrastructure, limited learning resources, and the lack of the role of student parents in understanding the concept of Free Learning learning.